Cover Picture: A Triptycene‐Based Porous Organic Polymer that Exhibited High Hydrogen and Carbon Dioxide Storage Capacities and Excellent CO2/N2 Selectivity (Chin. J. Chem. 5/2015). Issue 5 (May 2015) - Lu, Xi‐Long; Zhou, Tian‐You; Wu, Doufeng; Wen, Qiang; Zhao, Xin; Li, Qiaowei; Xiang, Qun; Xu, Jia‐Qiang; Li, Zhan‐Ting
<x xml:space="preserve">Abstract</x> The cover picture shows a novel porous organic polymer (POP) which was constructed through the condensation of triptycene tricatechol and 1, 3, 5‐benzenetris(4‐phenylboronic acid). POPs are a kind of organic materials which possess permanent porosity and thus have great potentials in the field of gas storage and separation. The as‐prepared triptycene‐ based POP exhibits high H2 uptake (up to 1.84 wt% at 77 K, 1 bar), large CO2 adsorption capacity (up to 18.1 wt% at 273 K, 1 bar), and excellent CO2/N2 adsorption selectivity (up to 120/1). The influence of solvent on the gas adsorption performance of the POP has also been investigated. More details are discussed in the article by Zhao et al. on page 539–544.